DIMENSI GEOGRAFI DALAM POLA PEMBAGIAN LAHAN (LODOK) PERTANIAN SAWAH BERBENTUK JARING LABA-LABA (SPIDERFIELD) DI DESA MELER KECAMATAN RUTENG KABUPATEN MANGGARAI - Udus, Godeliva Indryani; rahmawati, arfita; Wulakada, Hamza Huri (Universitas Nusa Cendana, 2024)
Pattern distribution land agriculture ricefield by ancestors Manggarai done in a way centered Where point the zero is in the middle land customary law will divided . ( 1) The land distribution system is viewed from social, economic and cultural aspects (2) rice field water distribution patterns and (3) strategies for preserving land distribution patterns. The research method used in this research is descriptive qualitative with data reduction and map analysis techniques. The results of this research show (1) fair distribution of rice fields helps reduce social and economic inequality in society . (2) There are springs located in the north and west ends which are channeled through irrigation program, so that many rice fields receive sufficient water, while rice fields in the eastern part can only be worked on during the rainy season Because lack water sources (3) Lodok has cultural heritage mark important that should preserved pattern distribution land This become an integral part of identity culture And tradition inherited locale to generation upcoming. Conclusion in study on Old Teno as Stakeholder Custom have right For control land that has been shared by old teno beforehand for the sake of interest together in order what has been inherited can become something that can beneficial for self Alone and others, Although there are two springs used for irrigation, the limited volume of the northern spring causes difficulties in irrigating rice fields in the easternmost part, especially during the dry season , Conservation Lodok No only involve holder custom And society, however Also supported by government through Service collaborative tourism with institution related For make Lodok as destination tourist.